Ag-catalyzed GaSb nanowires for flexible near-infrared photodetectors. (1st November 2022) - Sa, Zixu; Liu, Fengjing; Liu, Dong; Wang, Mingxu; Zhang, Jie; Yin, Yanxue; Pang, Zhiyong; Zhuang, Xinming; Wang, Peng; Yang, Zaixing
Abstract: High-quality narrow bandgap semiconductors nanowires (NWs) challenge the flexible near-infrared (NIR) photodetectors in next-generation imaging, data communication, environmental monitoring, and bioimaging applications. In this work, complementary metal oxide semiconductor-compatible metal of Ag is deposited on glass as the growth catalyst for the surfactant-assisted chemical vapor deposition of GaSb NWs. The uniform morphology, balance stoichiometry, high-quality crystallinity, and phase purity of as-prepared NWs are checked by scanning electron microscopy, energy dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, and X-ray diffraction. The electrical properties of as-prepared NWs are studied by constructing back-gated field-effect-transistors, displaying a high I on / I off ratio of 10 4 and high peak hole mobility of 400 cm 2 /(V·s). Benefiting from the excellent electrical and mechanical flexibility properties, the as-fabricated NW flexible NIR photodetector exhibits high sensitivity and excellent photoresponse, with responsivity as high as 618 A/W and detectivity as high as 6.7 × 10 10 Jones. Furthermore, there is no obvious decline in NIR photodetection behavior, even after parallel and perpendicular folding with 1200 cycles.